Photocatalytic Performance of Sm-Doped ZnO Prepared by Sonochemical Process - Anukorn Phuruangrat (2018)
© 2018, Pleiades Publishing, Ltd. Abstract: 0–3 wt % Sm-doped ZnO nanostructures were prepared by sonochemical process. The products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman spectroscopy and Fourier-transform infrared (FTIR) spectroscopy. In this research, the products were specified as oval particles of hexagonal wurtzite ZnO. Photocatalytic activities of the products were investigated by measuring the degradation of methylene blue (MB) under ultraviolet (UV) irradiation. Among them, the 3wt% Sm-doped ZnO product is a promising material for wastewater treatment.